PJMHS 2021
DOI: 10.53350/pjmhs211561903
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Outcome of Pregnancy with COVID-19: An Observational Study in Tertiary Care Hospitals of Pakistan

Abstract: Background: The new corona virus first appeared in Wuhan, China in December 2019 and has since spread around the world to other countries. The World Health Organization believes that this new CoV-19 epidemic is a public health emergency of international concern (PHEIC) on January 30, 2020Worldwide.The mortality rate of this viral infection ranges from 2% in Pakistan to 14.4% in Italy. Lympopenia, elevated transminase, proteinuria, increased LDH, and C-reactive protein levels are all common laboratory findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Low hemoglobin links to hypoxia, respiratory organ dysfunction, and therefore more adverse outcomes in COVID-19 infection. 16 In consideration of lymphocyte count, it is noteworthy that majority (60.7%) of women, exhibited normal lymphocyte counts, contradictory to finding of a study by Khan et al 7 , which reported a higher percentage (84%) of lymphocytopenia in pregnant women with COVID-19. A higher prevalence of lymphocytopenia was observed in the asymptomatic group compared to the symptomatic group (43.9% vs. 20.4%, with a p-value of 0.000), which is contradictory to the previous study where T lymphocytes and CD4+ T cell count below 200/ml revealed a significant relationship with symptomatology and mortality.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Low hemoglobin links to hypoxia, respiratory organ dysfunction, and therefore more adverse outcomes in COVID-19 infection. 16 In consideration of lymphocyte count, it is noteworthy that majority (60.7%) of women, exhibited normal lymphocyte counts, contradictory to finding of a study by Khan et al 7 , which reported a higher percentage (84%) of lymphocytopenia in pregnant women with COVID-19. A higher prevalence of lymphocytopenia was observed in the asymptomatic group compared to the symptomatic group (43.9% vs. 20.4%, with a p-value of 0.000), which is contradictory to the previous study where T lymphocytes and CD4+ T cell count below 200/ml revealed a significant relationship with symptomatology and mortality.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study majority of the pregnant women were found to be asymptomatic similar to other national and international studies where majority of the COVID-19 patients, pregnant and general population, were asymptomatic or presented with mild respiratory symptoms. [5][6][7] Fever, cough, and body ache were most common symptoms, 69.2%, 35.5%, and 34.6%, respectively. Similar to our results, local studies 8,9 and a study by Chen et al also identified fever and cough as its predominant clinical manifestations, 10 whereas sore throat, chest pain, loss of taste and smell, diarrhea and difficulty in breathing were few other symptoms reported in these study.…”
Section: Discussionmentioning
confidence: 99%
“…Although others were seen to have developed slight complications, as COVID-19 during pregnancy was associated with adverse fetal and maternal outcomes. 24,25…”
Section: Resultsmentioning
confidence: 99%
“…Through inhalation through the mouth or the nose, these aerosols might reach the lungs. The early phases of the COVID-19 epidemic are depicted in Table 1 (7).…”
Section: Outbreak Of Covid-19 Pandemic In Chinamentioning
confidence: 99%